Intracerebral arterial blood pressure in the vasculature distal to large vessel occlusions in patients with ischemic stroke: correlation with clinical and imaging parameters - Umhau, Moritz; Schmitt, Niclas; Jesser, Jessica; Hilgenfeld, Tim; Chen, Min; Ringleb, Peter A.; Möhlenbruch, Markus Alfred; Breckwoldt, Michael O.; Bendszus, Martin; Vollherbst, Dominik (Journal of neuroInterventional surgery, 2024)
Introduction Mechanical thrombectomy is a highly effective treatment for acute ischemic stroke (AIS) caused by large vessel occlusions (LVO). However, our understanding of the pathophysiology of AIS is still limited, particularly regarding the ischemic microenvironment distal to the occlusion. - Aim To investigate the relationship between the intracerebral blood pressure (BP) distal to an LVO and clinical and imaging parameters. - Methods In this single-center prospective study, intracerebral BPs proximal and distal to the occluding clot were measured during thrombectomy in patients with AIS of the anterior circulation caused by LVO. BPs were correlated with imaging parameters and clinical data using Spearman’s rank correlation and linear regression. - Results 25 patients were included. A significant correlation was found between the mean arterial pressure (MAP) distal to the occlusion and the baseline Alberta Stroke Program Early CT Score (Spearman r=0.503, P=0.014) and baseline National Institutes of Health Stroke Scale score (r=−0.439, P=0.036). No significant correlation was observed between the MAP distal to the occlusion and collateral scores (eg, MAP vs American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology score (r=0.307, P=0.165) or modified Rankin Scale (mRS) score (pre-mRS vs 90-day mRS; r=0.013, P=0.952)). Systemic MAPs did not correlate with the MAP distal to the clot (eg, R2=0.029, P=0.593). - Conclusion The intracerebral BP measured in the ischemic vasculature distal to the LVO correlates with the extent of the ischemic core and the clinical severity at baseline, but not with collateral scores, systemic BPs, or functional outcome. These results shed light on the pathophysiology of BP mechanisms in AIS and can be the basis for further research in this field.